2022
DOI: 10.1039/d1bm02015c
|View full text |Cite
|
Sign up to set email alerts
|

Tailored therapeutic release from polycaprolactone-silica hybrids for the treatment of osteomyelitis: antibiotic rifampicin and osteogenic silicates

Abstract: Polycaprolactone/silica hybrids offer a dual therapeutic effect: the promotion of bone regeneration thanks to silicate ions and strong antibacterial properties against the risk of osteomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…This could be attributed to the methyl and methylene groups in RFP. These results substantiate the loading of RFP in PCL−RFP NPs as previously verified by spectrophotometry [22] . The peaks are similar to reported studies on PCL [23] …”
Section: Resultssupporting
confidence: 91%
“…This could be attributed to the methyl and methylene groups in RFP. These results substantiate the loading of RFP in PCL−RFP NPs as previously verified by spectrophotometry [22] . The peaks are similar to reported studies on PCL [23] …”
Section: Resultssupporting
confidence: 91%
“…Consistently, it is worth noting that the sol–gel route, we used to synthesize silicate hybrids, is conducted under mild conditions and at room temperature, opening up new possibilities for doping with such compounds. Very recently, we succeeded in doping poly­(caprolactone)–silica hybrids with rifampicin for tailored therapeutic release of antibiotics in the treatment of osteomyelitis . Thus, our sol–gel process allows the introduction of fisetin in situ during the synthesis of BG–PCL hybrids.…”
Section: Introductionmentioning
confidence: 98%
“…Very recently, we succeeded in doping poly(caprolactone)–silica hybrids with rifampicin for tailored therapeutic release of antibiotics in the treatment of osteomyelitis. 16 Thus, our sol–gel process allows the introduction of fisetin in situ during the synthesis of BG–PCL hybrids. This doping-in-the-bulk technique contrasts with the usual adsorption techniques employed for organic loading, which commonly results in a nonsustainable release with an immediate burst of the loaded agent and limited long-term potential.…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative to develop innovative treatment methods. At present, a large number of antibiotic sustained-release materials have been developed to treat osteomyelitis ( Hasan et al, 2019 ; Xu et al, 2021 ; Feng et al, 2022 ; Gritsch et al, 2022 ; Wu et al, 2022 ), but the treatment effect is still not ideal and the recurrence rate is high. Zhou ( Zhang et al, 2023 ) et al reported Vancomycin-loaded silk fibroin microspheres in an injectable hydrogel for chronic osteomyelitis therapy, demonstrating a sustained-release profile and good biocompatibility, making it promising for application in osteomyelitis treatment.…”
Section: Introductionmentioning
confidence: 99%